Amine-reactive crosslinking enhances type 0 collagen hydrogel properties for regenerative medicine - Salthouse, Daniel; Goulding, Peter D.; Reay, Sophie L.; Jackson, Emma L.; Xu, Chenlong; Ahmed, Rochelle; Mearns-Spragg, Andrew; Novakovic, Katarina; Hilkens, Catharien M. U.; Ferreira, Ana Marina (Frontiers in Bioengineering and Biotechnology, 2024)
Collagen is extensively utilised in regenerative medicine due to its highly desirable properties. However, collagen is typically derived from mammalian sources, which poses several limitations, including high cost, potential risk of immunogenicity and transmission of infectious diseases, and ethical and religious constraints. Jellyfish-sourced Type 0 collagen represents a safer and more environmentally sustainable alternative collagen source. Thus, we investigated the potential of jellyfish collagen-based hydrogels, obtained from Rhizostoma pulmo (R. pulmo) jellyfish, to be utilised in regenerative medicine. A variety of R. pulmo collagen hydrogels (RpCol hydrogels) were formed by adding a range of chemical crosslinking agents and their physicochemical and biological properties were characterised to assess their suitability for regenerative medicine applications. The characteristic chemical composition of RpCol was confirmed by Fourier-transform infrared spectroscopy (FTIR), and the degradation kinetics, morphological, and rheological properties of RpCol hydrogels were shown to be adaptable through the addition of specific chemical crosslinking agents. The endotoxin levels of RpCol were below the Food and Drug Administration (FDA) limit for medical devices, thus allowing the potential use of RpCol in vivo. 8-arm polyethylene glycol succinimidyl carboxyl methyl ester (PEG-SCM)-crosslinked RpCol hydrogels preserved the viability and induced a significant increase in the metabolic activity of immortalised human mesenchymal stem/stromal cells (TERT-hMSCs), therefore demonstrating their potential to be utilised in a wide range of regenerative medicine applications.